Konsep Psikoterapi Islam: Tinjauan Literatur Sistematis - Pulungan, Muhammad Syukri; Siregar, Fithri Choirunnisa (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2024)
This research aims to explain the concept of Islamic psychotherapy through a systematic literature review method. The survey results show that mental health problems are a very important problem based on data showing that 15.5 million teenagers nationally experience mental health disorders. Based on the quantity of figures shown, it is equivalent to 2.45 million Indonesian teenagers. Anxiety disorders are the mental disorders most commonly suffered by teenagers, namely 3.7%. This is what underlies researchers' interest in researching the concept of Islamic psychotherapy as a form of assistance in dealing with mental health. The method used in this research is Systematic Literature Review by taking articles sourced from scopus.com. After the article was analyzed descriptively, it was found that there were at least two opinions about Islamic psychotherapy; firstly, that the concept of Islamic psychotherapy must be sourced from the Koran, Hadith and Muslim scientists, and the second opinion states that the concept of modern psychotherapy can be combined with Islamic values (Islamic perspective). However, everyone agrees on how important it is to apply Islamic psychotherapy to help with mental health problems